NEW ACTORS POUR ONTO STAGE - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
In many ACP States, the pressure of tourism is leading to hotel development and the establishment, or expansion, of 'nature reserves' for photo safaris and hunting. It causes land prices to rise. In Kenya alone, income from tourism reached US $450...